Toxic Effects Induced by Diuron and Its Metabolites in Caenorhabditis elegans - Lima, Thania Rios Rossi [UNESP]; Martins, Airton C.; Pereira, Lílian Cristina [UNESP]; Aschner, Michael (Springer Nature, 2022)
The toxicity of diuron herbicide and its metabolites has been extensively investigated; however, their precise toxic mechanisms have yet to be fully appreciated. In this context, we evaluated the toxic mechanism of diuron, 3,4-dichloroaniline (DCA) and 3-(3,4-dichlorophenyl)-1-methylurea (DCPMU), using Caenorhabditis elegans (C. elegans) in the L1 larval stage. For this purpose, worms were acutely exposed to the test chemicals with a preliminary concentration range of 0.5 to 500 μM and first analyzed for lethality (%). Next, the highest concentration (500 μM) was considered for survival (%), reactive oxygen and nitrogen species (RONS), glutathione (GSH) and ATP levels, autophagy index, behavior, and dopaminergic neurodegeneration parameters. Interestingly, increased lethality (%) was found for all chemicals at the higher concentrations tested (100 and 500 μM), with significant differences at 500 μM DCA (p < 0.05). A decrease in the median survival was observed mainly for DCA. Although no changes were observed in RONS production, GSH levels were significantly increased upon diuron and DCA treatment, likely reflecting an attempt to restore the redox status. Moreover, diuron and its metabolites impaired ATP levels, suggesting an alteration in mitochondrial function. The latter may trigger autophagy as an adaptive survival mechanism, but this was not observed in C. elegans. Dopaminergic neurotoxicity was observed upon treatment with all the tested chemicals, but only diuron induced alterations in the worms’ locomotor behavior. Combined, these results indicate that exposure to high concentrations of diuron and its metabolites elicit distinct adverse outcomes in C. elegans, and DCA in particular, plays an important role in the overall toxicity observed in this experimental model.
Keywords: C. Elegans; Chemical exposure; Diuron; Pesticides; Toxicity